Implementasi MetodeTakrir dalam Menghafal Al-Qur’an Jenjang Anak Usia Dasar di Islamic Center Medan - Rora Rizky wandini; Emeliya Sukma Dara Damanik; Sholihatul Hamidah Daulay (Institut Agama Islam Negeri (IAIN) Curup, 2020)
The basic age phase is a golden age for children. The Qur'an as a 'holy book' Muslims should be read, apprehended, cared for and memorized (QS.18:27). Prototype (basic concept) in memorizing it has spread in (QS. 75: 16-18). The application of (QS. 75: 16-18) can be done using the Takrir (repetitive) method. The role of parents, teachers and peers has a major impact on the process of memorizing Al Huffaz (memorization) of the Qur'an at the elementary age level. This research uses a qualitative-descriptive approach, with an insendental sampling technique. The subjects in this study were all of the Tahfidz / Tahfidzah Islamic Center Medan teachers who fostered elementary age children ranging from 5-9 years. Data collection is done by observation, interview and documentation. The results of this study indicate that (1) Takrir (repetitive) method as a prototype (basic concept) in memorizing the Qur'an at the basic age level in Islamic Center Medan (2) Takrir (repetitive) method is very effective to be used in forming Al Qur'an recitation at a level. primary age children in Medan Islamic Center (3) The role of parents, teachers and peers is very influential in the process of memorizing an Al Huffaz (memorizer) of the Qur'an at the basic age level at the Islamic Center Medan.